2014
DOI: 10.1155/2014/143450
|View full text |Cite
|
Sign up to set email alerts
|

Ecotin-Like ISP ofL. majorPromastigotes Fine-Tunes Macrophage Phagocytosis by Limiting the Pericellular Release of Bradykinin from Surface-Bound Kininogens: A Survival Strategy Based on the Silencing of Proinflammatory G-Protein Coupled Kinin B2and B1Receptors

Abstract: Inhibitors of serine peptidases (ISPs) expressed by Leishmania major enhance intracellular parasitism in macrophages by targeting neutrophil elastase (NE), a serine protease that couples phagocytosis to the prooxidative TLR4/PKR pathway. Here we investigated the functional interplay between ISP-expressing L. major and the kallikrein-kinin system (KKS). Enzymatic assays showed that NE inhibitor or recombinant ISP-2 inhibited KKS activation in human plasma activated by dextran sulfate. Intravital microscopy in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Similarly, all but one publications on Leishmania ecotin orthologs indicated that the main function of these proteins is protection against intestinal proteases in the gut of the insect Ecotin protects bacteria against human serum-mediated lysis vector, or against contact pathway-mediated bactericidal effects of the host [47,48], or downregulation of inflammatory monocytes and monocyte-derived cells [49]. We found only a single, very recent paper reporting that Leishmania donovani ecotin ortholog LnISP2 is not only a neutrophil elastase inhibitor, but also a MASP-2 inhibitor [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, all but one publications on Leishmania ecotin orthologs indicated that the main function of these proteins is protection against intestinal proteases in the gut of the insect Ecotin protects bacteria against human serum-mediated lysis vector, or against contact pathway-mediated bactericidal effects of the host [47,48], or downregulation of inflammatory monocytes and monocyte-derived cells [49]. We found only a single, very recent paper reporting that Leishmania donovani ecotin ortholog LnISP2 is not only a neutrophil elastase inhibitor, but also a MASP-2 inhibitor [40].…”
Section: Discussionmentioning
confidence: 99%
“…The blood pressure responses in whole conscious animal experiments depends on multiple physiological responses in addition to the differences in the nature, stability and quantities of Bk and [pS 6 ]Bk metabolites particularly produced during their passage through different tissues. We are currently examining the vascular activities of these kinins on hamster cheek pouch using intravital digital microscopy as previously reported [54,55], and the preliminary results indicate that [pS 6 ]Bk has 5% of Bk activity in plasma leakage and arteriolar dilatation. Further detailed pharmacological analyses of [pS 6 ]Bk metabolites resulting from the digestion by peptidases examined in the present work are necessary, as the experiments with des-(Arg 9 )-[pS 6 ]Bk on hamster cheek pouch, in which the preliminary experiments indicate that the plasma leakage was the main activity with low arteriolar dilatation.…”
Section: Discussionmentioning
confidence: 84%
“…With these findings we speculate that accumulation of IE in the placenta is an effective mean to induce local deprivation of B2R signal with implications on placental vasoregulation and on the engulfment and elimination of IE. In an elegant study employing mutant Leishmania major promastigotes that lack serine peptidase inhibitors (ISP) and consequently do not act in releasing BK from kininogen bound on the surface of macrophages, strongly suggest that B1R/B2R activation is suppressed due to inhibition of kinin-releasing serine protease activity operating as a parasite mechanism to reduce BK availability that in turn decreases pro-inflammatory responses to L. major infection (Svensjö et al, 2014). Thus, we propose BK sequestration by IE has a dual role in placental malaria.…”
Section: Discussionmentioning
confidence: 99%